Untreated red seaweed, Kappaphycus alvarezii as a biosorbent to remove Pb(II) ions from aqueous solution / Natalie James Solibun - James Solibun, Natalie (2015)
Present study has been undertaken to propose an alternative use of untreated red seaweed (UTRS), (Kappaphycus alvarezii) as biosorbent for the removal of heavy metal ions from aqueous solutions. The biosorption studies were conducted in batch adsorption system as a function of effect of pH, dosage and stirring rate. The experimental results showed that readily available Kappaphycus alvarezii was able to remove Pb(II) ions from aqueous solution. Based on the results obtained from the parameters investigated, the Pb(II) sorption capacity was 22.4215 mg/g at pH 5 for effect of pH, 6.15 mg/g (12.30 % of Pb(II) ions removal) at 0.02 g of biosorbent dosage for effect of biosorbent dosage, and 0.35 mg/g at 200 spm for effect of shaking rate. The Pb(II) sorption capacity in Kappaphycus alverazii increases as it follows these optimum values of pH 5, 0.02 g of biosorbent dosage and 200 spm of shaking rate. The Pb(II) sorption capacity was suppressed by the other cations present in the solution. The Pb(II) sorption equilibrium was better explained by Freundlich isotherm model with correlation coefficient of 0.9969. The results showed that this red seaweed can be a suitable alternative to use as biosorbent in the removal of toxic heavy metals from aqueous solutions.